Pengembangan Program Studi Umum pada Sekolah Tinggi Agama Islam Negeri (STAIN) - Nunu Ahmad An-Nahidl (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
The development of general education program at Islamic Religious Tertiary Education (PTAI) is feasible to conduct in order to meet the people’s demand, in addition to increase enrollment and improve the competitiveness of PTAI graduates. However, it also needs to make a re-arrangement on PTAI institutional management seriously. Firstly, it needs to formulate a standard rule which specifically governs clearly the organization of PTAI, including on how to regulate the conditions, process and legal base for PTAI when it is going to organize a general study program. Secondly, the pattern of concentration development or study program at PTAI should refer to the applicable statutory regulation, according to the scientific atmosphere of University, Institute, and Tertiary school, so it will not occur an overlapping between one and the other, and become clear also the respective domain of such institutions in educational development.